MitoNEET in Perivascular Adipose Tissue Blunts Atherosclerosis under Mild Cold Condition in Mice - Xiong, Wenhao; Zhao, Xiangjie; Garcia-Barrio, Minerva T.; Zhang, Jifeng; Lin, Jiandie; Chen, Y. Eugene; Jiang, Zhisheng; Chang, Lin (Frontiers in Physiology, 2017)
Background: Perivascular adipose tissue (PVAT), which surrounds most vessels, is de facto a distinct functional vascular layer actively contributing to vascular function and dysfunction. PVAT contributes to aortic remodeling by producing and releasing a large number of undetermined or less characterized factors that could target endothelial cells and vascular smooth muscle cells, and herein contribute to the maintenance of vessel homeostasis. Loss of PVAT in mice enhances atherosclerosis, but a causal relationship between PVAT and atherosclerosis and the possible underlying mechanisms remain to be addressed. The CDGSH iron sulfur domain 1 protein (referred to as mitoNEET), a mitochondrial outer membrane protein, regulates oxidative capacity and adipose tissue browning. The roles of mitoNEET in PVAT, especially in the development of atherosclerosis, are unknown. Methods: The brown adipocyte-specific mitoNEET transgenic mice were subjected to cold environmental stimulus. The metabolic rates and PVAT-dependent thermogenesis were investigated. Additionally, the brown adipocyte-specific mitoNEET transgenic mice were cross-bred with ApoE knockout mice. The ensuing mice were subsequently subjected to cold environmental stimulus and high cholesterol diet challenge for 3 months. The development of atherosclerosis was investigated. Results: Our data show that mitoNEET mRNA was downregulated in PVAT of both peroxisome proliferator-activated receptor gamma coactivator 1-alpha (Pgc1- and beta (Pgc1- knockout mice which are sensitive to cold. MitoNEET expression was higher in PVAT of wild type mice and increased upon cold stimulus. Transgenic mice with overexpression of mitoNEET in PVAT were cold resistant, and showed increased expression of thermogenic genes. ApoE knockout mice with mitoNEET overexpression in PVAT showed significant downregulation of inflammatory genes and showed reduced atherosclerosis development upon high fat diet feeding when kept in a 16oC environment. Conclusion: mitoNEET in PVAT is associated with PVAT-dependent thermogenesis and prevents atherosclerosis development. The results of this study provide new insights on PVAT and mitoNEET biology and atherosclerosis in cardiovascular diseases.